Transformation of Communication Media: An Analysis of The Effectiveness of The JKN Mobile App as an External Communication Channel in Reducing Information Asymmetry Among Participants - Rekha Wicakso; Ninis Agustini Damayani; Nindi Aristi (Jurnal Locus Penelitian dan Pengabdian, 2026)
Digital transformation has significantly changed the communication mechanisms of public healthcare services, particularly in improving information accessibility and reducing gaps between service providers and users. The National Health Insurance (JKN) program in Indonesia faces challenges in disseminating information effectively to millions of participants, resulting in information asymmetry regarding participants’ rights, obligations, and healthcare procedures. This study aims to analyze the effectiveness of the Mobile JKN application as an external communication channel and evaluate its contribution to reducing information asymmetry between BPJS Kesehatan and JKN participants. This research employed a quantitative approach using a cross-sectional survey design. Data were collected from 290 active JKN participants who had used the Mobile JKN application for at least three months. The research instrument was a structured questionnaire measured using a five-point Likert scale, while data analysis was conducted through descriptive statistics and Structural Equation Modeling (SEM). The results showed that Mobile JKN had high effectiveness as an external communication medium with an overall score of 3.67. The highest dimension was information accessibility (4.12), indicating that the application successfully improved participants’ access to healthcare information. Furthermore, the application reduced information asymmetry by 33.9%, particularly in improving participants’ understanding of their rights. However, challenges remained, including low digital literacy (43.8%), technical application problems (33.8%), and limited internet access (29.7%). This study concludes that Mobile JKN plays an important role in strengthening digital communication and reducing information disparities in public healthcare services. Continuous system improvement, digital literacy enhancement, and broader socialization strategies are required to optimize its effectiveness.